An activity theory-based exploration of “Eyeland”, a task-based serious game for EFL visually impaired students - Karen Villalba; Heydy Robles; Miguel Jimeno; Martha Cecilia Delgado-Cañas; Adriana Perez; Francisco Quintero (PeerJ Computer Science)
This study investigates how the Eyeland app, an accessible task-based serious game for English as a foreign language (EFL), can remediate traditional lessons for both visually impaired students (VISs) and sighted students (those without visual impairments) in a public high school in Colombia. Using an activity theory framework and its derived model, the Activity Theory-Based Model of Serious Games (ATMSG), the study explores the characteristics of traditional EFL lessons designed for these students, the adjustments made while integrating the Eyeland app, and the resulting changes in student experiences. The research employed action research cycles involving teachers in reflective processes that included planning, observing, acting, and re-planning to adapt and integrate Eyeland into the classroom. Qualitative research methods—field observations, focus groups, usability surveys, teacher interviews, and document analysis—were used to collect data and analyze how Eyeland was implemented and its effects on teaching and learning. Findings indicate that Eyeland effectively remediated traditional lessons by offering accessible, interactive features such as auditory, tactile, and visual support. These enhancements improved engagement for both sighted and visually impaired students. Traditional EFL lessons, which relied heavily on visual materials and teacher-centered methods, were transformed into more interactive, task-based activities that encouraged greater collaboration and student autonomy. Adjustments included redesigning lesson plans and rearranging classroom layouts to foster inclusion. Both sighted and visually impaired students reported positive experiences, particularly valuing the increased autonomy and engagement provided by Eyeland’s interactive tasks. The study highlights significant changes made to the lessons, with visually impaired students reporting predominantly positive experiences, though some teachers were reluctant to engage with the app. Eyeland contributed to the creation of inclusive classrooms by shifting from a teacher-centered approach to a student-centered learning environment that promoted better language learning outcomes. ATMSG was instrumental in analyzing how Eyeland fostered inclusive learning practices and provided valuable insights into re-mediation strategies, pedagogical planning, and the development of accessible content for EFL learners.